Vitamin D – a novel role in pregnancy - Arora Chander, P.; Hobel, C.J. (Вiopolymers and Cell, 2010)
Vitamin D regulates placental development and function. It is a potent regulator of the immune system- stimulating antimicrobial responses while suppressing inflammation. Its deficiency has been linked to increased risk of serious chronic and inflammatory diseases. Vitamin D deficiency during pregnancy increases susceptibility to infection and inflammation, leading, in turn, to outcome like preterm birth or preeclampsia. Pregnant women with darker skin pigmentation are more likely to be vitamin D deficient, particularly when living in regions with low exposure to sunlight. It is possible that during pregnancy, a primary non-infectious inflammatory process is activated by vitamin D deficiency. Combined assessment of vitamin D deficiency and inflammatory markers in early pregnancy or during different stages of pregnancy may facilitate the recognition of the risk of complications. Вітамін D регулює розвиток і функцію плаценти. Він є потужним регулятором імунної системи, що стимулює антибактерійну відповідь та пригнічує запалення. Його дефіцит при- зводить до зростання ризику серйозних хронічних і запальних захворювань. Протягом вагітності дефіцит вітаміну D підвищує сприйнятливість жінок до інфекцій і запалення, спричиняє передчасні пологи та прееклампсію. Вагітні жінки з темнішою пігментацією шкіри, які живуть у місцях з низьким рівнем сонячного світла, частіше страждають від дефіциту вітаміну D. При вагітності можлива активація первинного неінфекційного запального процесу внаслідок нестачі вітаміну D. Виявлення дефіциту вітаміну D і запальних маркерів на різних стадіях вагітності може полегшити розпізнавання ризику будь-яких ускладнень. Витамин D регулирует развитие и функцию плаценты. Он является мощным регулятором иммунной системы, стимулируя антибактериальный ответ и подавляя воспаление. Его дефицит приводит к увеличению риска серьезных хронических и воспалительных заболеваний. Во время беременности дефицит витамина D увеличивает восприимчивость женщин к инфекциям и воспалению, вызывает преждевременные роды и преэклампсию. Беременные женщины с более темной пигментацией кожи, живущие в областях с низким уровнем солнечного света, чаще подвержены дефициту витамина D. При беременности возможна активация первичного неинфекционного воспалительного процесса вследствие недостатка витамина D. Выявление дефицита витамина D и воспалительных маркеров на различных стадиях беременности может облегчить распознавание риска всевозможных осложнений.